Rare earth Dy activated Li3PO4:Dy phosphors for lyoluminescence dosimetry of ionizing radiations - Sahu, A K; Chowdhary, P S; Nayar, V; Dhoble, S J; Dubey, K K (Recent Research in Science and Technology, 2012)
Rare earth Dy doped Li3PO4 phosphate based phosphors were prepared by high temperature solid state diffusion technique. The peak LL intensity initially increases with increasing mass of the sample, then tends to attain a saturation value for higher mass of the solute added to the solvent. Eaelier experiments on gamma irradiated crystals have proved that the light emission originates from the recombination of released F-centres with trapped holes (V2-centres) at the liquid-solid interface.In this paper lyoluminescence(LL) characteristics of Li3PO4:Dy phosphors have been reported . These LL characteristics of Li3PO4 phosphor may be useful for high radiation dosimetry using LL technique.